Securing E.U. Democracy and Citizenship at what Costs? Reflections on Defence Spendings Between North-South and West-East Divergens - Laurențiu PETRILA; Felix Angel POPESCU; Ana-Maria COATU (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The events produced at the international level today demonstrate and track the recent evolution of the security environment of each member state of the European Union and beyond. The direct and indirect threats to regional and global security and stability require the taking, by the bodies empowered in this regard, of some precautionary measures and the improvement of the already existing military equipment at the level of each structure representing the military force of the states. In order to increase the sustainability and production capacity of the European Union, it is essential not only to increase, but also to optimize national and international investments in this field. This approach is necessary to achieve a significant change in strategy and to strengthen the joint capability to respond to critical needs.